Short Communication: Length-weight relationship and relative condition factor (Kn) of Selar crumenophthalmus (Bloch, 1973) from coastal waters of southeast coast of India - Anandaraj Perumal; Rajendran Narayanasamy; Yosuva Mariasingarayan (Aceh Journal of Animal Science, 2022)
The present work deals with length-weight relationship (LWRs) and relative condition factor of Selar crumenophthalmus. Totally 416 individuals of Bigeye scad were resolved for LWRs relationship, with 164 males and 252 females. This study recorded the minimum length of 16.5 cm corresponding to the weight of 29.9 g, and the maximum length of 24.6 cm corresponding to the weight of 179.7 g. The logarithmic exponent ‘b’ values remained greater than 3 and stated as 3.1 for males, 3.2 for females with correlation coefficient of 0.9415 and 0.9494 respectively at 5% level. The calculated relative condition factor (Kn) fluctuated from 0.89 to 0.98 with mean value of 0.95 ± 0.001 for males and in the range from 0.91 to 1.0 with mean of 0.96 ± 0.0008 for females. The Kn value remains as evident that the Bigeye scad was in healthy condition in the present study.